Paramedics' experiences of end-of-life care decision making with regard to nursing home residents: an exploration of influential issues and factors. Issue 10 (17th May 2016) - Murphy-Jones, Georgina; Timmons, Stephen
Abstract : Introduction: For a patient nearing the end of his or her life, transfer from a nursing home to the ED can be inappropriate, with potentially negative consequences, but transfer in these circumstances is, regrettably, all too common. There is a lack of published literature exploring how paramedics make decisions in end-of-life care situations. This study aims to explore how paramedics make decisions when asked to transport nursing home residents nearing the end of their lives. Methods: Phenomenological influenced design with a pragmatic approach. Semi-structured face-to-face interviews were conducted with six paramedics in an English NHS Ambulance Trust and subsequent data collected by text message. Audio-recorded interviews were transcribed verbatim and analysed using a thematic approach. Results: Three themes emerged in relation to the decision to transport patients from nursing homes to EDs in end-of-life care situations. Paramedics identified difficulties in understanding nursing home residents' wishes. When a patient no longer had the capacity for decision making, paramedics' reasoning processes were aligned to best interest decision making, weighing the risks and benefits of hospitalisation. Paramedics found it challenging to balance patients' best interests with pressure from others: nursing staff, patients' relatives and colleagues. Conclusions: A range of factors influence paramedics' decisions to transport nursing home residents to EDs in end-of-life care situations. Decision making became a process of negotiation when the patient's perceived best interests conflicted with that of others, resulting in contrasting approaches by paramedics. This paper considers how paramedics might be better trained and supported in dealing with these situations, with the aim of providing dignified and appropriate care to patients as they reach the end of their lives.